Impact of peritoneal reconfiguration on lymphocele formation after robot-assisted radical prostatectomy with pelvic lymph node dissection: a systematic review and meta-analysis of randomized controlled trials - Ditonno, Francesco; Manfredi, Celeste; Franco, Antonio; Veccia, Alessandro; Moro, Fabrizio Dal; De Nunzio, Cosimo; De Sio, Marco; Antonelli, Alessandro; Autorino, Riccardo (Prostate cancer and prostatic diseases, 2024)
Background Different strategies have been proposed to prevent lymphocele (LC) formation after radical prostatectomy (RARP) with pelvic lymph node dissection (PLND). According to several recently published randomized control trials (RCTs) on the topic, peritoneal reconfiguration appears to be associated with promising results. This systematic review aimed to assess the impact of peritoneal reconfiguration on LC formation in patients undergoing RARP and PLND. Methods A comprehensive bibliographic search was conducted in August 2023. Studies assessing patients with prostate cancer undergoing RARP with PLND (P) and concomitant peritoneal reconfiguration (I) compared or not with other techniques (C) to prevent LC formation (O) were included. Original prospective and retrospective studies (S) were selected. LC and symptomatic LC rates were chosen as co-primary outcomes. Only RCTs were included in the meta-analysis. Results Eleven studies investigating 2991 patients were included in the systematic review, and five RCTs evaluating 1712 subjects were deemed eligible for meta-analysis. Peritoneal flap (PF) was the most common surgical technique used for LC prevention (9 studies). A significantly lower likelihood of LC was observed after PF (OR 0.82, 95% CI 0.27–1.37, I 2 = 74.54%), with no significant difference in terms of symptomatic LC (OR 0.21, 95% CI −0.41–0.84, I 2 = 0%). Probability of LC-related complications (OR 0.36, 95% CI 0.04–0.67, I 2 = 0%), Clavien-Dindo ≥ 3 overall complications (OR 0.61, 95% CI 0.21–1.0, I 2 = 0%), and Clavien-Dindo ≥ 3 LC-related complications (OR 0.98, 95% CI 0.29–1.67, I 2 = 0%) were significantly lower after PF. Conclusions PF after RARP with PLND reduces LC formation, LC-related complications, and severe postoperative adverse events.